Barriers to the Implementation of Learning Organization in Private Universities - Hendrawati, Titi; Firdiansyah, Firdiansyah; Humaeni, Ayatullah (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Implementing the concept of learning organization in private universities is a big problem. This article highlights potential barriers to transforming private colleges into responsive, innovative, and learning-oriented organizations. These barriers include a strict corporate culture, insufficient resources, lack of leadership support, vague goals, and difficulty managing change. However, the article also provides ways to overcome these challenges, such as developing a learning culture, wise resource allocation, dedicated leadership, explicit goal setting, and effective change management. By implementing these solutions, private universities can become dynamic and relevant educational institutions, ready to meet the changing demands of the education sector. This article demonstrates the important function of a learning organization in improving the quality of higher education and preparing students for a competitive future. The purpose of this study is to examine the barriers to the implementation of learning organization and describe the solutions to these barriers. Descriptive qualitative and case study methodology through data collection through interviews, observations, and document analysis to find out more about the implementation of a learning organization and its impact on the performance of private universities.The findings of this study are intended to show the importance of developing a learning organization in a higher education environment as well as dealing with barriers to implementation.Â